Crocetin and Its Glycoside Crocin, Two Bioactive Constituents From Crocus sativus L. (Saffron), Differentially Inhibit Angiogenesis by Inhibiting Endothelial Cytoskeleton Organization and Cell Migration Through VEGFR2/SRC/FAK and VEGFR2/MEK/ERK Signaling Pathways - Zhao, Chen; Kam, Hio-Tong; Chen, Yan; Gong, Guiyi; Hoi, Maggie Pui-Man; Skalicka-Woźniak, Krystyna; Dias, Alberto Carlos Pires; Lee, Simon Ming-Yuen (Frontiers in Pharmacology, 2021)
Crocetin and crocin are two important carotenoids isolated from saffron (Crocus sativus L.), which have been used as natural biomedicines with beneficial effects for modifying suboptimal health status associated with abnormal angiogenesis. However, the anti-angiogenic effects and the possible underlying mechanisms of the effects of crocetin and crocin have not been investigated and compared. The anti-angiogenic effects of crocetin and crocin were tested on human umbilical vein endothelial cells (HUVECs) in vitro and zebrafish in vivo. In vivo, crocetin (20 μM) and crocin (50 and 100 μM) significantly inhibited subintestinal vein vessels formation, and a conversion between them exsited in zebrafish, resulting in the difference of their effective concentrations. In HUVECs model, crocetin (10, 20 and 40 μM) and crocin (100, 200 and 400 μM) inhibited cell migration and tube formation, and inhibited the phosphorylation of VEGFR2 and its downstream pathway molecules. These results suggested that crocetin was more effective than crocin to inhibit angiogenesis through the regulation of VEGF/VEGFR2 signaling pathway. These compounds, especially crocetin, are potential candidates to serve as natural biomedicines in the management of diseases associated with abnormal blood vessel growth such as age-related macular degeneration.